TINGKAT PENGUASAAN TATA BAHASA BAKU BAHASA INDONESIA OLEH GURU BAHASA INDONESIA DI KABUPATEN LAMONGAN - Markub Markub; Laila Tri Lestari (MEDIA DIDAKTIKA, 2019)
The general objective of this study is to describe the level of mastery of grammar Baku Indonesian by Indonesian teachers in Lamongan , comparing the level of mastery TBBBI by teachers at any educational institution, and rank the most difficult grammar for Indonesian teachers in Lamongan. This study was designed in a quantitative descriptive study. The source of research data is a teacher Indonesian (elementary, middle, and high school) in Lamongan. Analyzing data is performed quantitative research. The results showed that the level of mastery TBBBI by elementary school teachers belong less with a mean score of 45, the level of mastery TBBBI by Indonesian teachers SMP classified as moderate with a mean score of 59, and the level of mastery TBBBI by Indonesian high school teachers were moderate with a mean score of 63. Comparison of the TBBBI mastery by an elementary school teacher, junior high school teacher and high school teacher is 45:59:63. Traveler grammatical difficulties for Indonesian teachers are as follows. For primary school teachers ranked the highest difficulty is the word order (score of 37), followed by successive syntax (score of 47) and a sound system (score of 52). For junior high school teacher, the highest rank of difficulty is the syntax (score of 54), followed by successive order of words (score 59) and a sound system (score of 63). For high school teachers, the highest rank of difficulty is the syntax (score of 60), followed by successive order of words (score 64) and a sound system (score of 66).